Analyze The Impact Of Islamic Work Ethic On Maslahah-Based Job Performance And Islamic Family Well-Being - Sudirman, Iman Fauzi (Jurnal Ilmiah Ekonomi Islam, 2024)
Achievement of employee performance is often a problem because it has an impact on the progress of the company. Then work and family relationships are inseparable for employees because they are interrelated. The Islamic work ethic views work as a means to improve oneself economically, socially, psychologically, and well-being that emanates from faith. And this research is related to Islamic work ethic in work and family. This research aims to determine the impact of Islamic work ethic on maslahah-base job performance and Islamic family wellbeing by examining the mediating role of intrinsic motivation and job satisfaction. This type of research uses a quantitative description with explanatory research using a sample of 207 respondents. The data analysis method used in this research is descriptive analysis method, Structural Equation Modeling (SEM) with SmartPLS 3 software. The results show that Islamic work ethic has a significant and positive effect on maslahah-based job performance and Islamic family wellbeing both directly and indirectly The role of the variables of intrinsic motivation and job satisfaction is to partially mediate.